The biology and control of wild oats (Avena spp.) in the Western Cape - Cairns, A. L. P.(Andrew Lawrence Patrick) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric) -- University of Stellenbosch, 1974.